Evaluation of soybean genotypes for resistance to rust disease (Phakopsora pachyrhizi) - APRI SULISTYO; SUMARTINI SUMARTINI (Society for Indonesian Biodiversity, 2016)
Sulistyo A, Sumartini. 2016. Evaluation of soybean genotypes for resistance to rust diseaseÂ (Phakopsora pachyrhizi).Â  Biodiversitas 17: 124-128. Pest and disease are one of limiting factor in soybean cultivation in Indonesia. One of the diseases that canreduce soybean production is rust diseases caused by Phakopsora pachyrhizi. The use of resistant varieties can reduce yield losses dueto this disease. The aim of this study was to evaluate the resistance of soybean genotypes to rust disease and to study the interactionbetween agronomic traits with rust disease on soybean genotypes. This study was conducted at a screen house of the IndonesianLegumes and Tuber Crops Research Institute (ILETRI)Â  in Malang, Indonesia from April to July 2015. A total of 10 soybean genotypesconsist of eight lines and two varieties (Argomulyo and Grobogan).Â  The experiment was arranged as randomized completely block design with four replications. Eachgenotype planted in five plastic pots for each replicate. Three weeks after planting, all plants were inoculated with rust disease.Inoculation was done by spraying a suspension of spores (spore density of 10Â 4Â spore mL-1)Â  to the surface of leaves. Observations werecarried out on rust disease severity based on the method of International Working Group on Soybean Rust rating system, days toflowering, plant height, number of branches, number of fertile nodes, number of pods, and seed weight per plant. The results showedthat all genotypes classified as moderately resistant to rust disease. In this study, days to flowering and plant height influence thedevelopment of rust disease severity. There are three lines that have seed weight per plant significantly heavier than Argomulyo (4.97 g) and Grobogan (4.30 g), namely K/I100//B63///G-7 (6.55 g),Â K/I100//B63///G-8 (6.15 g), andÂ I100/B54//A-5 (5.85 g). The high value ofÂ the scales of seed weight per plant for the three lines is supported by high-performance plants with a lot of number of fertile nodes and pods. These three soybean genotypes potentially serve as genetic material to develop high yielding soybean varieties and resistant to rust disease.